A clinical neurological, neurophysiological, and neuropsychological study of sheep farmers and dippers exposed to organophosphate pesticides - Jamal, G (BMJ Group, 2002)
Objectives: To classify clinical diseases of the subjects with abnormal indices of peripheral neuropathy identified in field studies of sheep farmers and dippers exposed to organophosphate pesticides. To explore what neuropsychological profiles, if any, may be associated with neurophysiological damage in these subjects. Methods: A case-control study (79 subjects) nested within the cross sectional study (685 subjects) of sheep farmers from the field study. Three groups with no, possible, and probable or definite neuropathy according to field studies were recruited. Investigations comprised symptoms of neuropathy, neurologial signs, motor and sensory nerve conduction, electromyography, quantitative sensory testing, and neuropsychological tests. Results: The incidence of clinical neuropathy increased from 7% in the no neuropathy group to 52% in the probable or definite neuropathy group based on nerve conduction measurements or presence of neurological signs. Sensory abnormalities were found more often than motor deficits. Small diameter nerve fibres were also affected more than large fibres. Conclusions: The neuropathy is predominantly sensory and is characteristic of distal, chronic neuropathy with no acute features. Small fibre populations are affected more than large fibre populations. Increasing severity of neuropathy was associated with anxiety and depression as measured in the neuropsychological tests.